Case study of Keith Haring's illustrations and techniques in realization of local experimental animation - Syaryfah Fazidawaty, binti Wan Busrah (Universiti Malaysia Sarawak (UNIMAS), 2009)
This research emphasized on the study of illustrations and techniques by Keith Haring. Based on the case study, complete observation on Haring's style of illustrations and existed experimental animation was conducted to have a clear understanding on how to create a great experimental music video animation with simple illustration. As a result, a new experimental animation in local context had been created